Study on the State of Methane Molecule Adsorption on Different Media in Highly Evolved Marine Shales—A Case Study on the Shales From the Lower Silurian Longmaxi Formation in the Sichuan Basin, Southern China - Jiang, Lin; Song, Yan; Liu, Wenping; Chen, Zhiyuan; Zhang, Hanbing; He, Fangyu (Frontiers in Earth Science, 2022)
The major sedimentary basins in China contain abundant shale gas resources to be explored, and the exploration of shale gas has received more attention in recent years. Shale gas exists mainly in two states, i.e., free and adsorbed. The latter mainly exists on the surface of media, including organic matter and clay minerals, etc., but its adsorption state remains unknown. In this paper, we take the Longmaxi Formation marine shale in the southern Sichuan Basin of southern China as the research object. The state of methane molecule adsorption on different media in marine shales is analyzed by conducting mineral composition analysis, TOC content analysis, isothermal adsorption experiments, FIB-SEM, and FIB-HIM experiments on the core samples referring to previous research. The conclusions are as follows: the adsorbed gas mainly exists in the organic-matter pores, which feature excellent roundness and connectivity with a large number of small pores inside like a hive. The surface of the organic matter contains many adsorption sites, featuring strong adsorption capacity and making methane molecules continuously distributed on the internal surface of the organic-matter pores. The organic matter has a large specific surface area and is lipophilic, which offers an ideal condition for the adsorption of methane molecules. Part of the adsorbed gas exists in the pores of clay minerals, which are lamellar and triangular. The surface of clay minerals contains fewer adsorption sites, featuring poorer adsorption capacity and making methane molecules discontinuously distributed on the surface of the clay minerals. The clay minerals have a smaller specific surface area than the organic matter, thus featuring a smaller space for adsorption. The clay minerals are hydrophilic. In addition to methane molecules, mixed-layer illite/smectite (I/S) and chlorite also adsorb water molecules. The illite surface adsorbs mainly water molecules and, to a lesser extent, methane molecules. Finally, the adsorption state patterns of methane molecules on organic matter and clay minerals were summarized.